Memory feedback controller design for stochastic Markov jump distributed delay systems with input saturation and partially known transition rates. (February 2015) - Zhao, Junjie; Wang, Jing; Park, Ju H.; Shen, Hao
Abstract: This paper considers the problem of stabilization for a class of stochastic Markov jump distributed delay systems with partially known transition rates subject to saturating actuators. By employing local sector conditions and an appropriate Lyapunov function, a state memory feedback controller is designed to guarantee that the resulted closed-loop constrained systems are mean-square stochastic asymptotically stable. Some sufficient conditions for the solution to this problem are derived in terms of linear matrix inequalities. Finally, a numerical example is provided to demonstrate the effectiveness of the proposed method.